Preface: 2024 International Conference on Law, History, Philosophy and Public Relations (LHPPR 2024) - Zephaniah, Mortimer; Cheng, Xiaohua (Transactions on Social Science, Education and Humanities Research, 2024)
The 2024 International Conference on Law, History, Philosophy and Public Relations (LHPPR 2024) was successfully held in Manchester, United Kingdom from July 30-31, 2024. This conference brought together innovative scholars and experts in the fields of law, historical research, philosophy, public relations, gender studies, and social sciences to a common forum. The main purpose of the conference is to promote research and development activities. Another goal is to promote the exchange of information among researchers, developers, experts, students, and practitioners worldwide. These multi-faceted disciplines are converging very fast. LHPPR 2024 received many submissions and all papers included into this collection have undergone careful peer-review by at least two reviewers before being selected for publication. We would like to thank the organization staff, the committee members, all the reviewers and everyone who had worked for and lending a hand in reviewing papers and making valuable suggestions for the improvement of the conference. We’d like to express our gratitude for all authors and participants of this conference. The LHPPR Organizing Committees Manchester, United Kingdom